Cucumber, Armenian—Cucumis melo L. (Flexuosus group) - James M. Stephens (EDIS, 2003)
This document provides an overview of the Armenian cucumber (Cucumis melo L., Flexuosus group), detailing its botanical characteristics, cultivation practices, and uses. Although closely related to muskmelon, the fruit resembles a cucumber in shape and is often grown for novelty or pickling. It thrives in warm climates and is typically planted in early spring or fall in Florida. The plant is susceptible to common diseases like powdery and downy mildew. The document also highlights the fruit’s unique appearance and growth patterns, including its twisted shape and muskmelon-like aroma when ripe. Original publication date May 1994.